Physics : investigate the forces of nature - Gardner, Jane P. (Inquire and investigate., 2014)
Provides an introduction to physics, explaining how skateboarders use force and motion to perform tricks, how gravity determines the path of a baseball throw, and how electricity is used to power toasters and put on rock shows.